Implementasi Ajaran tentang Pernikahan Berdasarkan I Korintus 7 di Kalangan Gembala Sidang Gereja Pantekosta di Indonesia, Kabupaten Jember - Kanti Widiastuti; Els Rampisela (Sekolah Tinggi Teologi Baptis, Jakarta, 2020)
Marriage was God's idea from the very beginning of human creation, and it began first in the garden of Eden. Even though God's purpose for Christian marriage is a lifetime, in reality, not a few Christian households experience conflicts and result in divorce. This study aims to apply the teachings about marriage based on 1 Corinthians 7. The method used is qualitative with a hermeneutical approach to 1 Corinthians text 7. The implementation of the text is applied to 28 GPdI siding pastors in Jember city, using a questionnaire instrument. The results of the study are presented in the form of description, analysis, and interpretation, with the conclusion that the level of implementation of the teachings of the apostle Paul regarding the notion of marriage based on 1 Corinthians 7 among pastors of the GPdI session in Jember Regency was 82.71%, and was in the